TMOD-18. TARGETING THE PI3K/AKT PATHWAY IN MYCN AMPLIFIED HIGH GRADE GLIOMAS. (9th November 2020) - Halligan, Katharine; Stanton, Ann-Catherine; Halbert, Matthew; Golbourn, Brian; Mack, Stephen; Pollack, Ian; Agnihotri, Sameer
Abstract: Pediatric glioblastoma (pGBM) are incurable brain tumors with overall poor prognosis and response to treatments due to molecular and epigenetic heterogeneity. In particular, the MYCN subtype of pGBM are a highly aggressive form of GBM with a dismal median survival of only 14 months. Furthermore, this subtype is enriched with loss of the tumor suppressor genes TP53 and PTEN, leading to aberrantly active PI3K-AKT signaling pathway and DNA-checkpoint abnormalities. Here, we report the generation of a novel syngeneic mouse model that recapitulates the features of the MYCN subtype of pGBM. We isolated Sox2-Cre neural stem cells from C57BL/6 mice and transduced inverted retroviral-cassettes of the murine Mycn oncogene simultaneously with shRNA targeting tumor suppressor genes p53 and Pten . Retroviral-cassettes are flanked by tandem LoxP sites arranged so that Cre recombinase expression inverts the cassettes in frame allowing for MYCN protein expression and loss of the P53/PTEN proteins. Transgene activation is accompanied with selectable cell surface markers and fluorescent tags enabling for fluorescent activated cell sorting (FACS) of the desired cell populations. Neural stem cells with MYCN protein expression and concurrent silencing of P53 and PTEN protein (NPP cells) result in significantly increased proliferation and activation of PI3K-AKT pathway as compared to control neural stem cells and have. Injection of NPP cells into the forebrain of immune competent C57BL/6 mice result in the formation of invasive high-grade gliomas with a lethal phenotype at ~50 days post injection. Using several next generation brain penetrant small molecule inhibitors of the PI3K-AKT pathway, we show inhibition of tumorigenesis in vitro . Moreover, we have identified several novel mechanisms of PI3KAKT treatment resistance and are currently identifying therapies that may overcome this resistance through RNA seq analysis. In summary, well defined genetic drivers of GBM can lead to informed mouse model generation to test promising therapies.